2013
DOI: 10.5603/cj.a2017.0142
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous origin of culprit coronary arteries in acute coronary syndromes

Abstract: The most frequently encountered AOCCA is LCx branching-off from RCA. AOCCA may either be difficult to cannulate and PCI aborted even in STEMI, or missed, especially when the intermediate branch from LCA is mimicking proper LCx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Anomalous origin of right coronary artery from the left coronary sinus and the origin of left circumflex artery from the right coronary sinus are the most common coronary anomalies . Nonetheless, a few patients present with atherosclerotic-related disease, and they may be asymptomatic . In a study of more than 126 000 individuals, anomalous origin of a coronary artery was identified in less than 1%, and none of these patients presented with an acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anomalous origin of right coronary artery from the left coronary sinus and the origin of left circumflex artery from the right coronary sinus are the most common coronary anomalies . Nonetheless, a few patients present with atherosclerotic-related disease, and they may be asymptomatic . In a study of more than 126 000 individuals, anomalous origin of a coronary artery was identified in less than 1%, and none of these patients presented with an acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…1 Nonetheless, a few patients present with atherosclerotic-related disease, and they may be asymptomatic. 4,5 In a study of more than 126 000 individuals, 5 anomalous origin of a coronary artery was identified in less than 1%, and none of these patients presented with an acute coronary syndrome. Anomalous coronary arteries may trigger intermittent ischemia to which the mechanism is complex and not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Unless patients have presented in early life with angina, the discovery of the CAA in patients with acute coronary syndrome is incidental ( 2 ). To date, there is only 1 other reported case of a patient presenting with 1) an anterior ST-segment elevation myocardial infarction (STEMI) from 2) a culprit lesion in the LAD that is anomalous with the 3) left coronary artery arising from the right coronary sinus ( 6 ). Performing PCI in patients with CAAs is challenging and carries an increased risk of ostial dissection ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…1B). The left anterior descending coronary artery (LAD) supplies segments 1,2,7,8,13,14, and 17, the right coronary artery (RCA) supplies segments 3, 4, 9, 10, and 15, while the left circumflex coronary artery (LCx) supplies segments 5, 6, 11, 12, and 16 [11]. However, coronary arteries may be anomalous and their anatomy varies from patient to patient, creating a limitation of the AHA model [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%